(27x+3+9x-5)/2=10x-2

Simple and best practice solution for (27x+3+9x-5)/2=10x-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (27x+3+9x-5)/2=10x-2 equation:



(27x+3+9x-5)/2=10x-2
We move all terms to the left:
(27x+3+9x-5)/2-(10x-2)=0
We add all the numbers together, and all the variables
(36x-2)/2-(10x-2)=0
We get rid of parentheses
(36x-2)/2-10x+2=0
We multiply all the terms by the denominator
(36x-2)-10x*2+2*2=0
We add all the numbers together, and all the variables
(36x-2)-10x*2+4=0
Wy multiply elements
(36x-2)-20x+4=0
We get rid of parentheses
36x-20x-2+4=0
We add all the numbers together, and all the variables
16x+2=0
We move all terms containing x to the left, all other terms to the right
16x=-2
x=-2/16
x=-1/8

You can always share this solution

See similar equations:

| (6p+16)=7 | | 1x-54=25 | | 2x-11=9-3x | | 7/2xQ=1 | | 3?92? b=31? b?7 | | 5/8Xa=1 | | 1/6x————=5/2 | | -12x=-15x+-36 | | (Z=4)19-2z | | 2x+7x+x=180° | | 8n^2+8n-576=0 | | 4x+21+4x=3x-14 | | -(-9x+1)=10 | | -2x-2=34 | | 7y+2=5y+26 | | V=12x11/3 | | -y+12-2y=2 | | -5x+23=13 | | 8.6=2.1?1.3y | | 3x-3=-84 | | 6-4•n=12 | | x-4-3x=10-6 | | -x/5+4=13 | | -13.5/x=-2.50 | | 8^x=2x+2 | | 2x-6=4x-36 | | 42÷m=7 | | y+-13=-8 | | 5y-(-17)=33 | | 2x+5=12x*10 | | –2s+–9=–1 | | S=t2+4 |

Equations solver categories